A Comparative Study of Corporate Rehabilitation in Nigeria and United Kingdom - Bankole, Fisayo; Musa-Agboneni , Omomen (ABUAD Law Journal, 2019)
As a company grows from infancy to adulthood, there may come moments where the company may fall ill- that is in distress, this illness at times may point towards the direction of liquidation or winding up the activities of the company, which in the literal sense, signifies the death of the company. It may however not be economically beneficial nor shareholders friendly that the company be allowed to collapse. The company may then begin to seek a means of survival despite its indebtedness. The idea of corporate rehabilitation is thus, premised on the exigency to keep an ailing company as a going concern. This paperexamines the relevant laws in Nigeria and how effective they have been able to provide sustainable survival mechanics for ailing companies in Nigeria. Also, the paper compared the Nigerian corporate rehabilitation procedures with that of the United Kingdom(UK). The study revealed that the present legal framework for companies in Nigeria, especially the Companies and Allied Matters Act (CAMA) does not provide sufficient support system for ailing companies. It concludes that CAMA does not measure as a dependable legal framework for corporate rehabilitation, on the scale of international best practice. It found that UK has a more developed legal framework for corporate rescue; as a consequence, the Company’s Voluntary Arrangement and Administration are two convenient corporate rescue/ rehabilitation mechanisms which could serve asmodels for developing a concrete corporate rescue regime in Nigeria.